Gene frequencies of BoLA-DRB3 alleles estimated through sequence-based typing (PCR-SBT) in a Holstein population of La Pampa province (Veterinary Science, 2017)
The objective of this study was to estimate allele frequencies of the BoLA-DRB3 exon 2 in a Holstein population from La Pampa province. The exon 2 polymorphisms were genotyped by sequence-based typing method (PCR-SBT). In the studied herd, a total of 21 variants were detected, ranging from 0.014 to 0.222. This resulted in an expected heterozygocity of 0.91. Obtained data were compared with those reported for Japanese Holstein population, showing that with the exception of BoLA-DRB3*1201 allele, both populations shared the same major variants (BoLA-DRB3*1101, *1501 and *0101). This result could be consequence of the high level of homogeneity present in Holstein breed, due to the use of same genetic on the whole world.
Keywords: BoLA-DRB3; Polymorphism; Sequence-based typing